Organic Acid Exudation by Ectomycorrhizal Fungi in Responce to Aluminium - Kanwal, Harpreet Kaur (My University, 2007)
Different ectomycorrhizal fungi (MAR, h1, Pt-P and Pt-N) were screened for their tolerance to Aluminium. The fungal cultures were grown in MMN media (pH 4.5) having different concentrations of Al (0, 50, 100, 150, 200 and 250 µg/ml of Al). The growth pattern of fungi, pH of culture filtrate, acid phosphatase activity and organic acid exudation were studied. The growth of fungi decreased with an increase in Al concentration. The maximum growth was observed in case of Paxillus involutus (MAR), followed by Pt-N. Pt-P and h1 were found to be sensitive to Aluminium. The acid phosphatase activity increased as the concentration of Al increased in the medium. A negative correlation between pH of filtrate and Al concentration was observed, which concluded that acids were formed during the period of exposure of fungi to Aluminium. Oxalic acid was the main acid that was produced in large amounts by these ectomycorrhizal fungi in response to Al. Organic acid tolerance mechanism was studied in these cultures through the amounts of organic acids produced in these fungal cultures by RP-HPLC. It was found that organic acid exudation mechanism operates in h1, while in Pt-P, Pt-N it is absent. In MAR, the mechanism is operative only upto a limited extent. Also, a cultivation method was developed to enable exposure of ectomycorrhizal plants with intact extramatrical mycelium to media solutions containing different concentrations of aluminium. Populus deltoides was micropropagated through tissue culture and micropropagated plants were colonized with Paxillus involutus (MAR). The plants were transferred to test tubes containing glass beads along with MMN media (pH 4.5). Paxillus involutus (MAR) was inoculated near the roots. Different concentration of Al (0, 100, 150, 200 and 250µg/ml) in the form of Al2(SO4)3.16H2O were added afterwards and the plantlets were grown for 30 days. The amount of organic acids in mycorrhizal and non-mycorrhizal systems was measured by withdrawing filtrates from the solution and analyzing by RP-HPLC. It was observed that levels of oxalic acid were significantly higher in mycorrhizal treatments than in non-mycorrhizal controls. Thus, the results obtained suggest that production of oxalic acid is stimulated by exposure to elevated Al in case of mycorrhizal plants colonized by MAR. Thus, the tolerance mechanism of organic acid exudation operates in case of mycorrhizal Populus deltoides
Keywords: Acid Exudation; Ectomycorrhizal; Acid Phosphatase; Paxillus Involutus